Landuse Change Dynamics and Green Open Space Allocation Strategy Based on Environmentally Sound Regional Budgeting (A Case Study of Bekasi City) - Suwarli .; R.P. Santun Sitorus; Widiatmaka .; Eka Intan Kumala Putri; Kholil . (Forum Pasca Sarjana, 2012)
Marginalization issue of green open space (ruang terbuka hijau/RTH) with a high level of land conversion to built space in urban area shows that there is no commitment of regional government on a sustainable urban development. Political commitment on the regional government is indicated among others by the weak support of green regional budgeting (APBD) related to RTH. The research was conducted in Bekasi City. The purpose of this research was to determine a model of environmentally sound regional budgeting policy strategy related to allocation of public RTH by using a hard systems and a soft stems approaches. The former was conducted by landuse changes analysis with the factors influencing them, by designing a regional budgeting based on RTH allocating model structure by using a dynamic system approach and to formulate the direction policy using focus group discussion (FGD) and analytical hierarchy process (AHP). The results of landuse change analysis showed that there was an increase in built land area from 5,5% (1.157,77 ha) in 1989 to 70,7% (14.879,85 ha) in 2009. The determinants of landuse changes in RTH were population, educational facilities, markets, supermarkets, ettlements, industries, restaurants, hotels, and inns (R2 = 99,8%). The dynamic model also designed three scenarios of RTH allocating policy strategy (pessimism, moderate, and optimism) with a early simulation in 2010. The optimism scenario was considered as being capable of accommodating the fulfillment of city RTH need really on an assumption of considerable long multiyears budgeting so that in 2030 the target of 20% public RTH would be achieved. The results of analysis by AHP and FGD approaches showed that alternatives were on 2 main policies, namely: agriculture/RTH infrastructure development and RTH land acquiremen.